(untitled) (Mugda Medical College Journal, 2025)
A cross-sectional, observational study was conducted in Dhaka Medical College Hospital (DMCH), Dhaka, Bangladesh, between January 2016 and June 2018, to determine the shortterm outcome of acute ischemic stroke with aspiration pneumonia (AP). Patients who were suffering from acute ischemic stroke (AIS) and were admitted under the Departments of Medicine, Neurology and Neurosurgery were approached for inclusion in the study. Detail history taking and physical examination were done. For analysis, total population were subdivided into two groups: group A (AIS with AP) and group B (AIS without AP). All patients in both groups (43 patients from group A and 44 patients in group B) were interviewed, examined and followed up for 2 weeks. Data related to the sociodemographic characteristics and risk factors were observed. Outcome was assessed by Modified Rankin Scale (MRS) score: ‘0’ = no symptoms at all; ‘1’ = no significant disability; ‘2-5’= slight to severe disability; and ‘6’ = death. Out of 87 patients, mean age of group A and group B patients were 63.86±10.92 years and 60.89±9.75 years respectively. A male preponderance was observed, i.e., 76.7% and 70.5% males in group A and group B respectively. Among group A patients, 51.2% were smokers and 4.7% were alcoholics, while among group B patients, 45.5% were smokers and 4.5% were alcoholics. In group A, 60.5% were hypertensive, 32.6% were diabetic, 11.6% had coronary artery disease (CAD) and 55.8% had family history of stroke. In group B, 59.1% were hypertensive, 25% were diabetic, 11.4% had CAD and 34.1% had family history of stroke. Initial NIH Stroke Score (NIHSS) ³21 was found more prevalent in group A than that of group B patients (51.2% vs. 13.6%; p<0.001). However, after two weeks, group B had higher proportion of patients having modified Rankin scale (MRS) score 0–2 than that of group A (47.7% vs. 9.3%; p<0.05). A higher proportion of group A patients having MRS score 3-5 than that of group B (55.8% vs 45.5%; p>0.05). MRS score 6 at week two implied that the patients were deceased (34.9% vs. 6.8%; p<0.05). The relative risk of aspiration pneumonia for leading to death within 2 weeks was 5.11 (95% CI 1.59-16.42) (p<0.001) Aspiration pneumonia is a predictor of worse outcome in acute ischemic stroke patients and imposes a 5-times increased risk of death within 2 weeks. Mugda Med Coll J. 2025; 8(1): 8-12